Legal Responsibilities of Extraordinary Members (ALB) as a Substitute Notary in Making Deeds - Dedy Stansyah (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2025)
The position of Extraordinary Members (Anggota Luar Biasa/ALB) of the Indonesian Notary Association (INI) as Substitute Notaries during internship activities carries strategic significance and legal implications. ALBs who have fulfilled the necessary requirements may be appointed to temporarily carry out a notary’s duties, offering them valuable experience and skill development. This study seeks to examine the legal standing of ALBs in such roles and how these internship activities are implemented. Employing a normative juridical approach, the research is based on Law Number 2 of 2014 concerning the Position of Notaries and the notary profession's code of ethics. The findings show that although ALBs possess limited authority, they are legally accountable for every deed they produce during their appointment. Each notarial deed must explicitly mention the status of the ALB as a Substitute Notary, in accordance with the applicable legal provisions. Any deviation from proper procedures can lead to the deed being legally defective or declared null and void. Therefore, the role of ALBs as Substitute Notaries must be exercised with caution and adherence to professional ethics. In addition, the position of ALBs in internship activities as Substitute Notaries also influences the violations committed as substitute notaries.